Effective Learning of Pancasila Education through Technology-Based Interactive Media for Elementary School Students - Istiqomah, Lailatul; Wibowo, Setiawan Edi (FKIP Universitas Lampung, 2024)
Effective Learning of Pancasila Education through Technology-Based Interactive Media for Elementary School Students . Objective: This study aims to evaluate the effectiveness of technology-based interactive learning media in improving students' motivation, engagement, and learning outcomes in Pancasila Education subjects in elementary schools. Methods: This study used a mixed-methods approach, combining descriptive qualitative analysis with a pretest-posttest experimental design. The research was conducted at SDN Semarangan 4 and SDN Krapyak in Godean Sub-district, Yogyakarta, involving 54 grade 5 students selected by purposive sampling. Data collection techniques used questionnaires, observations, interviews, and pretest-posttest assessments. Findings: The results showed a significant increase in student learning outcomes (20.36%), activeness (18.24%), and motivation (14.64%) in the use of technology-based interactive media in learning Pancasila education. This finding is in line with constructivist theory which states that technology-based interactive media can improve students' understanding of abstract concepts through multisensory learning experiences, such as animations interactive games, and active learning. Conclusion: The application of innovative learning media in learning Pancasila education can help students in improving students' activeness, motivation, and learning outcomes. In addition, the use of interactive media helps teachers in meeting students' learning needs. This study emphasizes the need for targeted training and better access to technology to ensure the successful implementation and sustainability of interactive learning media. Keywords: interactive learning media, Pancasila education, technology-based, effective learning.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024135